2019
DOI: 10.2166/bgs.2019.924
|View full text |Cite
|
Sign up to set email alerts
|

Real time control schemes for improving water quality from bioretention cells

Abstract: Extreme weather and the proliferation of impervious areas in urban watersheds increases the frequency of flood events and deepens water quality concerns. Bioretention is a type of green infrastructure practice developed to mitigate these impacts by reducing peak flows, runoff volume, and nutrient loads in stormwater. However, studies have shown inconsistency in the ability of bioretention to manage some pollutants, particularly some forms of nitrogen. Innovative sensor and control technologies are being tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Free draining have shown good results at literature, but are domintated by aerobic conditions and lack to perform both nitrification and denitrification [42][43][44]. Therefore, bioretention cells with interal water storage promote aerobic and anaerobic conditions favoring both nitrification and denitrification [13,45].…”
Section: Bioretentionmentioning
confidence: 99%
See 2 more Smart Citations
“…Free draining have shown good results at literature, but are domintated by aerobic conditions and lack to perform both nitrification and denitrification [42][43][44]. Therefore, bioretention cells with interal water storage promote aerobic and anaerobic conditions favoring both nitrification and denitrification [13,45].…”
Section: Bioretentionmentioning
confidence: 99%
“…The author used two low-cost implementation strategies for both new cells and for cells already built and found that bioretention with RTC can mitigate the negative effects of short and long dry periods and mitigate the influence that large inflow volumes have on the treatment of faecal microbes. [13] analyzed several RTC schemes in bioretention columns to improve water quality. The most notable water quality improvement was related to nutrients, while the static system performed best to ammonium by more than 40% and columns with internal water storage removed more nitrate by more than 73%.…”
Section: Bioretentionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a historical context, LID initially aimed to reintegrate excess runoff into the hydrological cycle [10]. With the advances of techniques, LID incorporated objectives of mitigating the impacts caused by climate change, in addition to proposing to reintegrate the runoff volume into the catchment through local reuse [11,12]. Therefore, incorporating medium-and long-term time scales, considering the increased occurrence of extreme flood and drought events and aiming at the recycling and co-management of resources, LIDs can contribute to several United Nations Sustainable Development Goals (UN SDG), specifically, the objectives of zero hunger (SDG 2), clean water and sanitation (SDG 6), affordable and clean energy (SDG 7), sustainable cities and communities (SDG 11) and climate action (SDG 13).…”
Section: Introductionmentioning
confidence: 99%
“…LID practices provide reductions in peak flow and diffuse pollution through physicalchemical processes, such as filtration and drainage layers at the systems [10]. However, despite the most varied designs, these systems are projected to function passively, i.e., they do not adapt the system configurations over time to optimize aerobic, anaerobic and/or hydraulic processes at the layers [12].…”
Section: Introductionmentioning
confidence: 99%